Incidência e tratamento dos cistos. - de Carvalho, P. S.; Sanches, M. G.; del Nery, S. T. (My University, 1990)
The records of 78 patients (1978-1987 period) submitted to surgical treatment of cysts, were analysed to verify the cyst location, etiology, types of cysts, and surgical techniques. There were made commentaries and orientations on the necessity of radiography, cytological and histopathological examination and post-operative radiological control.
Incidence and treatment of cysts
Keywords: Brazil; female; human; jaw cyst; male; English Abstract; Female; Human; Jaw Cysts; Male